Mental budgeting and the financial management of small and medium entrepreneurs - Mohammed Ziaul Hoque (Cogent Economics & Finance, 2017)
The present study examines the influences of mental budgeting on the financial management of SMEs, via a survey of SME owners' practices regarding various issues in financial management. The samples of 201 SMEs were randomly selected from the city of Chittagong, Bangladesh and interviewed using a structured questionnaire and the data have been analysed using descriptive statistics, principal component analysis and ordinal logistic regression. The results of the study show that own savings and loans from relatives are the major sources of the business capital with micro-credit coming in the second place. The earnings from existing business were mostly used to meet family expenditures. The results also show that Mental Budgeting (MB) and its determinants like other sources of income over existing business, never spending more than a fixed amount, having an overview of checking balance, long-term future orientation and financial product knowledge have significant influences on the financial management of SMEs. However, no evidences of several aspects were found in the same field.
Keywords: 330; mental accounting; mental budgeting; financial management; SMEs; behavioural finance; effects